THE EFFECT OF DRILLING TOWARD STUDENTS VOCABULLARY IN SIDOMUKTI VILLAGE GRESIK - Gadis Dinda Finissha; Nisa Fitri Amalia; Slamet Asari; Andi Rahmad Rahim; Sukaris Sukaris; Nur Fauziyah (Universitas Muhammadiyah Gresik, 2021)
The aims of this study to know student vocabulary through drill vocabulary on second grade Elementary school in Sidomukti village, Kebomas Gresik. The participant from Elementary School until Junior high school and the enthusiastic of participant is good around 25-30 in every meeting. Classroom activity was made fun but still get knowledge through game and material worksheet based on topic. Then drilling method that is applied in the classroom, students not only listen theory but try to answer question in worksheet. Researcher want to make more relaxed learning atmosphere in every meeting in order to student did not bored, researcher try to guide student from worksheet to increase their vocabulary. Vocabulary is the one of focus in this learning, their ability in vocabulary is variative because they are from different level Elementary School and Junior High School. Every meeting we try to drill their vocabulary so we hope their vocabulary increase step by step. We try to drill their vocabulary in every meeting to recognize some of vocabulary related with the material and also try to make student motivated for answer the question. This research method using pre-test and post-test for retrieve data .The result from this learning is participant happy and enjoy, their vocabulary ability and their vocabulary increase also.